Diplostomum von Nordmann, 1832 (Digenea: Diplostomidae) in the sub-Arctic: descriptions of the larval stages of six species discovered recently in Iceland - Faltýnková, Anna; Georgieva, Simona; Kostadinova, Aneta; Blasco-Costa, Isabel; Scholz, Tomáš; Skírnisson, Karl (Systematic parasitology, 2014)
Frequent infections with Diplostomum spp. (Digenea: Diplostomidae) were found in the freshwater snail Radix peregra (Müller) and three fish species, the salmonids Salmo trutta fario L., Salvelinus alpinus (L.) and the gasterosteid Gasterosteus aculeatus L., collected in four lakes in south-western Iceland in 2012. Detailed analysis of the isolates integrating molecular, morphological and ecological data revealed that these belong to Diplostomum spathaceum (Rudolphi, 1819) and five putative new species (three infecting both snails and fish). This paper provides detailed descriptions of the metacercariae of the six species-level lineages of Diplostomum spp. and of the cercariae of three of the lineages discovered in Iceland with comments on the application of ITS1 rDNA for species distinction within Diplostomum von Nordmann, 1832 in the light of the novel data. We strongly suggest the use of molecular evidence based on cox1 gene sequences (in addition to ITS1-5.8S-ITS2 sequences) in association with detailed assessment of the morphology of the larval stages in future studies of Diplostomum spp. in fish and snails.
Keywords: Island; larva; hlemýždi; druhová specificita; cerkárie; Trematoda; Animals; Cercaria; Lakes; Phylogeny; Snails; Species Specificity; fylogeneze; jezera; Salmonidae; Larva; Iceland; zvířata